Nanofiber air filtering material and preparation method thereof

By using electret materials such as barium titanate and lithium niobate in air filter materials and blending and antibacterial materials such as titanium dioxide and zinc oxide, the problems of electrospinning materials with single functions are solved, and high efficiency is achieved. Long-term filtration and antibacterial effects are suitable for improving the durability of air filter materials.

CN119139811AInactive Publication Date: 2024-12-17CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411650612.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing electrospinning filter materials are prone to attenuation during use, resulting in short filtration effect and single function, which cannot effectively improve the durability and antibacterial properties of air filter materials.

Method used

By independently controlling multiple electrospinning nozzles, composite nanofiber air filter materials blended with electret nanomaterials and antibacterial nanomaterials are prepared in one step, using electret materials such as barium titanate and lithium niobate, as well as titanium dioxide and zinc oxide. The spinning solution is prepared separately and electrospinning is controlled separately to form self-charged antibacterial nanofiber materials.

Benefits of technology

It significantly improves the electrostatic durability and filtration efficiency of the material, and achieves efficient filtering of fine particles and bacteria in the air. It has long-term electret and antibacterial effects. The porosity and fiber diameter are within an excellent range, which is suitable for practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119139811A_ABST
    Figure CN119139811A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrostatic spinning, in particular to a nanofiber air filtering material and a preparation method thereof. A preparation method of a nanofiber air filtering material comprises the following steps: preparing an electret material spinning solution, dispersing an electret material in a first solvent, then adding a first polymer, and stirring until the electret material is completely dissolved to obtain the corresponding electret material spinning solution; the particle size of the electret material is 20 nm to 100 nm; preparing an antibacterial material spinning solution, dispersing an antibacterial material in a second solvent, then adding a second polymer, and stirring until the antibacterial material is completely dissolved to obtain the corresponding antibacterial material spinning solution; the particle size of the antibacterial material is 20 nm to 100 nm; preparing a nanofiber air filtering material, and performing electrostatic spinning to obtain the nanofiber air filtering material. The electret material spinning solution and the antibacterial material spinning solution are independently supplied. The fiber synthesized by the preparation method of the nanofiber air filtering material is high in quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrospinning, and in particular to a nanofiber air filter material and a preparation method thereof. Background Art

[0002] Seeking for efficient, antibacterial and multifunctional air filtration materials has always been a research hotspot in the field of air pollution control and human health and safety protection.

[0003] Traditional electret fiber filter materials can use the static charge on the fiber surface to capture fine particles, achieving the purpose of high efficiency and low resistance, but the static charge tends to decay quickly and become ineffective, resulting in a short service life. Electrospinning can directly inject charges during the fiber curing stage. The prepared nanofiber membrane has the advantages of high porosity, through holes, micron to submicron pore size and high surface adsorption energy, and can efficiently filter fine dust. However, there are also problems such as rapid increase in filtration pressure drop and easy decay of static charge, and the existing electret fiber filter materials have relatively single functions. At present, air filter materials are in urgent need of further improvement in terms of function. Summary of the invention

[0004] The purpose of the present application is to provide a nanofiber air filter material and a preparation method thereof, by independently controlling a plurality of electrospinning nozzles to prepare a composite nanofiber air filter material blended with an organic polymer, an electret nanomaterial and an antibacterial nanomaterial in one step, thereby solving the problems of low electrostatic persistence and easy failure of existing electrospinning nanofiber filter materials in actual use, greatly improving the durability of the material, and at the same time the material also has an antibacterial effect.

[0005] The present application provides a method for preparing a nanofiber air filter material, comprising the following steps: Prepare an electret material spinning solution, disperse an electret material in a first solvent, then add a first polymer, and stir until the first polymer is completely dissolved to obtain a corresponding electret material spinning solution; wherein the electret material spinning solution includes one electret material spinning solution or several electret material spinning solutions, and the particle size of the electret material is 20nm~100nm; Prepare an antibacterial material spinning solution, disperse an antibacterial material in a second solvent, then add a second polymer, stir until the second polymer is completely dissolved, and obtain a corresponding antibacterial material spinning solution; wherein the antibacterial material spinning solution includes one antibacterial material spinning solution or several antibacterial material spinning solutions, and the particle size of the antibacterial material is 20nm~100nm; To prepare the nanofiber air filter material, the electret material spinning solution and the antibacterial material spinning solution are simultaneously electrospun to obtain the nanofiber air filter material; wherein the electret material spinning solution is supplied independently, and the antibacterial material spinning solution is supplied independently.

[0006] When the electret material is two or more electret materials, each electret material spinning solution is prepared separately to obtain a corresponding electret material spinning solution, and then the spinning process is also controlled and supplied separately. When the antibacterial material is two or more antibacterial materials, each antibacterial material spinning solution is prepared separately to obtain a corresponding antibacterial material spinning solution, and then the spinning process is also controlled and supplied separately.

[0007] Preferably, the electret material is barium titanate and / or lithium niobate.

[0008] Preferably, the antibacterial material is titanium dioxide and / or zinc oxide.

[0009] Preferably, the first solvent is a dimethylformamide solution, a mixture of dimethylformamide and acetone, or a mixture of dimethylformamide and tetrahydrofuran, and the second solvent is a dimethylformamide solution, a mixture of dimethylformamide and acetone, or a mixture of dimethylformamide and tetrahydrofuran.

[0010] Preferably, the amount of the electret material added is 0.5%~2.5% of the mass of the electret material spinning solution, the amount of the antibacterial material added is 0.5%~2.5% of the mass of the antibacterial material spinning solution, the mass concentration of the first polymer in the electret material spinning solution is 8%~14%, and the mass concentration of the second polymer in the antibacterial material spinning solution is 8%~14%.

[0011] Preferably, the first polymer is polyacrylonitrile and / or polyvinylidene fluoride, and the second polymer is polyacrylonitrile and / or polyvinylidene fluoride.

[0012] Preferably, the electret material spinning solution is independently supplied through a first injection pump, a first syringe, a first conduit and a first needle which are independently arranged in sequence; The antibacterial material spinning solution is independently supplied through a second injection pump, a second syringe, a second catheter and a second needle which are independently arranged in sequence.

[0013] Preferably, the DC voltage of the electrospinning process is 10 kV to 20 kV, the receiving distance is 7 cm to 20 cm, the spinning solution flow rate is 0.5 mL / h to 1 mL / h, and the moving speed of the moving device is 100 cm / min to 400 cm / min. The moving device is loaded with a needle.

[0014] The present application also provides a nanofiber air filter material, which is the nanofiber air filter material prepared according to any of the above-mentioned preparation methods.

[0015] Preferably, the porosity of the nanofiber air filter material is 80% to 90%, the thickness is 10 μm to 30 μm, and the average fiber diameter is 190 nm to 600 nm.

[0016] The nanofiber air filter material provided by the present application is a self-charging antibacterial nanofiber air filter material. Lithium niobate and barium titanate are both excellent ferroelectric piezoelectric materials with low dielectric loss and extremely high dielectric constant, as well as unique quasi-static electric field and long-term charge storage capacity, which can spontaneously polarize and have excellent electret performance. Polyacrylonitrile and polyvinylidene fluoride are organic polymer electret materials with excellent performance. Blending them with barium titanate or lithium niobate ferroelectric piezoelectric nanoparticles can improve the electret effect of the composite material. Compared with a single nanofiber material, the composite material of the present application generates an electric charge under the contact separation force, prevents the charge failure problem caused by long-term storage or changes in environmental factors such as humidity, can self-charge, has higher electrostatic persistence, has better filtering effect, and space charge is easily captured during the preparation process.

[0017] Titanium dioxide and zinc oxide can stimulate oxygen in the air to become active oxygen under the irradiation of sunlight, especially ultraviolet light, and react with various microorganisms to kill bacteria. In addition, zinc ions will gradually become free. When they come into contact with bacteria, they will combine with the active protease in the bacteria to make it inactive, thereby killing the bacteria.

[0018] In the prior art, one or more materials are used when electret materials are used. When multiple materials are mixed with polymers, they tend to agglomerate and disperse unevenly, thus affecting the performance of the obtained material. The present application prepares the corresponding spinning solutions separately, and then controls the electrostatic spinning separately, so that the material particles and the polymer are mixed more evenly, ensuring the excellent electret effect and filtering effect of the nanofiber air filter material, and having high operability in actual production.

[0019] The beneficial effects of this application are: 1. The preparation method of the nanofiber air filter material of the present application prepares the corresponding spinning solutions respectively, and then controls each spinning solution independently, and electrospins at the same time, so that the material particles and the polymer are mixed more evenly, which effectively avoids the uneven dispersion of the material particles. The synthesized fiber is of high quality and the material properties are stable.

[0020] 2. The preparation method of the present application controls electrostatic spinning to prepare composite nanofiber air filter materials. The electret material is preferably barium titanate and / or lithium niobate, which has lower dielectric loss and extremely high dielectric constant and long-term charge storage capacity than other materials. It will spontaneously polarize and become electret. The preparation method of the present application can achieve the effect of one-time spinning and permanent electret. After being placed for a long time, self-charging and long-term electret can be achieved by simple tapping, and the filtration efficiency has hardly changed.

[0021] 3. The nanofiber air filter material of the present application can self-charge, has excellent electret effect and filtering effect, the material porosity is 80%~90%, the thickness is 10μm~30μm, the average fiber diameter is 190nm~600nm, and can filter solid particles, aerosols, viruses and bacteria in the air. Among them, the filtration efficiency of sodium chloride aerosol with a median particle size of 0.075±0.02μm is above 95%, the filtration pressure drop is 50~100Pa, the electrostatic persistence is higher, and it also has an antibacterial effect and a high antibacterial rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram of a multi-needle electrospinning device. Among them, 1-micro injection pump, 2-translation device, 3-high voltage power supply, 4-receiving screen, 5-receiving screen roller, 6-receiving screen roller and translation device controller, 7-needle, 8-catheter, 9-syringe, 10-receiving screen bracket.

[0023] Figure 2 These are SEM photos of composite nanofiber materials, the left one is magnified 500 times, and the right one is magnified 5000 times.

[0024] Figure 3 TEM images of the fibers, (a) is the TEM image of PAN / TiO2, and (b) is the TEM image of PAN / BaTiO3.

[0025] Figure 4 Schematic diagram of the contact and separation piezoelectric performance test of composite nanofiber materials. Among them, 11-polytetrafluoroethylene plate, 12-fiber membrane, 13-linear motor, 14-electrometer, 15-negative electrode of electrometer power supply, 16-positive electrode of electrometer power supply, 17-copper foil strip, 18-polypropylene spunbond non-woven fabric.

[0026] Figure 5 This is the contact separation output voltage diagram of the composite nanofiber material of Example 1 on the 7th day. DETAILED DESCRIPTION

[0027] The present application is further described below in conjunction with specific embodiments. The following examples are used to illustrate the present application, but are not intended to limit the scope of the present application. Without departing from the spirit and substance of the present application, modifications or replacements made to the present application method, steps or conditions all belong to the scope of the present application. The first, second, etc. terms in the present application are only used for descriptive purposes and cannot be interpreted as indicating or suggesting relative importance.

[0028] Unless otherwise specified, the materials and reagents used in the examples are conventional commercially available materials and reagents, and the technical means used in the examples are conventional means well known to those skilled in the art.

[0029] A method for preparing a nanofiber air filter material comprises the following steps: (1) dispersing the electret material in a first solvent, then adding a first polymer, stirring until the first polymer is completely dissolved, to obtain a corresponding electret material spinning solution, wherein the particle size of the electret material is 20nm~100nm; dispersing the antibacterial material in a second solvent, then adding a second polymer, stirring until the second polymer is completely dissolved, to obtain a corresponding antibacterial material spinning solution, wherein the particle size of the antibacterial material is 20nm~100nm.

[0030] Among them, the electret material can be barium titanate, lithium niobate, silicon dioxide, tourmaline, apatite, aluminum oxide, barium oxide, ferroferric oxide, tantalum pentoxide, lead zirconate titanate, silicon nitride, boehmite nanoparticles, etc., preferably barium titanate and / or lithium niobate, both of which have lower dielectric loss and extremely high dielectric constant and long-term charge storage capacity than other materials, and will spontaneously polarize and electret. The preparation method of this application can achieve one-time spinning and permanent electret effect. The particle diameters of the electret material and the antibacterial material are both 20~100 nm. If the particle diameter is too small, it is easy to agglomerate and difficult to disperse in the spinning solution. If the particle diameter is too large, it is easy to affect the mixing effect, and it is not easy to form a stable dispersion and easy to settle. The addition amount of the electret material is 0.5%~2.5% of the mass of the electret material spinning solution, and the addition amount of the antibacterial material is 0.5%~2.5% of the mass of the antibacterial material spinning solution. If the addition amount is too high, it is easy to agglomerate. The first polymer can be polyacrylonitrile, polyvinylidene fluoride, polytetrafluoroethylene, polystyrene, ethyl cellulose, chitosan, etc., preferably polyacrylonitrile and / or polyvinylidene fluoride, and the second polymer can be polyacrylonitrile, polyvinylidene fluoride, polytetrafluoroethylene, polystyrene, ethyl cellulose, chitosan, etc., preferably polyacrylonitrile and / or polyvinylidene fluoride. Polyacrylonitrile contains a cyano (—CN) group, which has a strong polarity, so that it is easy to form a strong dipole force between molecules, it is easy to form a dipole charge, and improve the electrostatic adsorption performance of the filter material. In polyvinylidene fluoride, C-F bonds and C-H bonds have large dipole moments, high dielectric constants, low dielectric losses, and good dielectric properties. In addition, these two polymers can be dissolved in organic solvents, have good spinnability, and have good chemical stability and thermal stability. The mass concentration of the first polymer in the spinning solution is 8%~14%, and the mass concentration of the second polymer in the antibacterial material spinning solution is 8%~14%. The greater the mass concentration of the polymer, the larger the fiber diameter prepared. If the mass concentration exceeds this range, the spinning cannot be done, and if it is below this range, the fiber cannot be formed.

[0031] (2) Preparing a nanofiber air filter material, electrospinning the electret material spinning solution and the antibacterial material spinning solution simultaneously to obtain the nanofiber air filter material; wherein the electret material spinning solution is supplied independently, and the antibacterial material spinning solution is supplied independently.

[0032] The electret material spinning solution is one or several, the first injection pump includes one or several, and each electret material spinning solution is supplied independently; similarly, the antibacterial material spinning solution is one or several, the first injection pump includes one or several, and each electret material spinning solution is supplied independently.

[0033] Each needle is evenly arranged and fixed on the mobile device. Each needle is connected to the positive electrode of the power supply, and the receiving device is connected to the negative electrode of the power supply. It should be noted that there are many types of electrospinning devices with the above structure and capable of achieving the above functions, and they can also be homemade devices, such as Figure 1 The multi-needle electrospinning device shown includes 18 needles 7 (arranged 6×3), each needle 7 is connected to an independent syringe 9 through a catheter 8, and each syringe 9 is controlled by an independent microinjection pump 1 (the microinjection pump 1 is arranged in a rectangular housing indicated in the figure). Here, the syringe 9, the catheter 8 and the needle 7 only represent the setting relationship of the relevant components, and do not specify the specific corresponding relationship. The needles 7 are arranged in parallel and fixed on the bracket of the translation device 2. The needles 7 are connected to the positive electrode of the high-voltage power supply 3, and the receiving screen 4 is connected to the negative electrode of the high-voltage power supply 3. The receiving screen 4 is driven to adjust the position by the receiving screen roller 5. The roller speed of the receiving screen roller 5 and the translation speed of the translation device 2 are controlled by the receiving screen roller and the translation device controller 6. A receiving screen bracket 10 is arranged below the receiving screen 4. The DC voltage of the electrospinning process is 10 kV~20 kV, the receiving distance is 7 cm~20 cm, the spinning solution flow rate is 0.5 mL / h~1 mL / h, and the moving speed of the moving device is 100 cm / min~400 cm / min.

[0034] When two spinning solutions are used for electrospinning, the two spinning solutions are respectively injected into different independently controlled syringes, connected to the needles by conduits, and the needles are evenly distributed. Preferably, different spinning solutions in the same row and column are arranged at intervals, that is, the spinning solutions in the needles adjacent to them are different. When more than two spinning solutions are used for electrospinning, each spinning solution is respectively injected into different independently controlled syringes and connected to the needles by conduits, and the needles are evenly distributed. Preferably, different spinning solutions in the same horizontal row are arranged in sequence, and different spinning solutions in different horizontal rows are arranged in front and back in a staggered manner, which is conducive to realizing uniform distribution of electret particles and antibacterial particles inside the film. However, the more needles are used, the greater the interference between the needles, which is not conducive to spinning. Therefore, it is more appropriate to set two or three rows of needles during electrospinning.

[0035] The nanofiber air filter material prepared according to any of the above-mentioned preparation methods has an average fiber diameter of 190nm~600nm, and a thickness of 10μm~30μm. If the thickness exceeds this range, the filtration pressure drop increases significantly, and if it is below this range, it cannot achieve excellent filtration effect and antibacterial effect. The porosity of the nanofiber air filter material is 80%~90%. When the porosity is below this range, the filtration resistance increases, and when the porosity is above this range, the filtration efficiency decreases.

[0036] Example 1 A method for preparing a nanofiber air filter material comprises the following steps: (1) Weigh 9 g of dimethylformamide solvent and place it in a 30 mL wide-mouth reagent bottle. Under magnetic stirring conditions, slowly add 0.2 g of the electret material BaTiO3 (average particle size of 50 nm) to 9 g of dimethylformamide solvent to obtain a dispersion. After ultrasonic treatment for 60 min using an ultrasonic cleaner, add 1 g of polyacrylonitrile powder, magnetically stir in a 45°C constant temperature water bath for 12 h, and then ultrasonically treat for 2 h to mix evenly until the first polymer is completely dissolved to obtain a PAN / BaTiO3 spinning solution; Weigh 9g of dimethylformamide solvent and place it in a 30mL wide-mouth reagent bottle. Under magnetic stirring conditions, slowly add 0.2g of antibacterial material TiO2 (average particle size of 30nm) to 9g of dimethylformamide solvent to obtain a dispersion. After ultrasonic treatment for 60 min using an ultrasonic cleaner, add 1g of polyacrylonitrile powder, stir magnetically in a 45℃ constant temperature water bath for 12h, and then ultrasonically treat for 2h to mix evenly until the second polymer is completely dissolved to obtain a PAN / TiO2 spinning solution.

[0037] (2) The obtained PAN / BaTiO3 spinning solution and PAN / TiO2 spinning solution are respectively controlled by independent injection pumps for spinning, and each of the injection pumps is connected to the syringe, catheter and needle in turn. The amount of PAN / TiO2 spinning solution and PAN / BaTiO3 spinning solution is 5 mL. A flat-head metal injection needle with an inner diameter of 0.6 mm is used, and each syringe is controlled by an independent injection pump for spinning. The needles are arranged in parallel and fixed on the bracket of a horizontally reciprocating translation device. At the same time, electrospinning is performed with the following parameters: spinning solution flow rate is 0.5 mL / h, spinning distance is 14 cm, spinning voltage is 18 kV, translation device moving speed is 220 cm / min, and receiving device rotation speed is 100 rpm. Electrospinning is deposited on the receiving screen to obtain a nanofiber air filter material composite of PAN / TiO2 and PAN / BaTiO3, such as Figure 2 As shown in Figure 1, its thickness is 25 μm, the porosity is 84.5%, the average fiber diameter is 572 nm, and the TEM image of the fiber is shown in Figure 1. Figure 3 As shown, it can be seen that the material uses polyacrylonitrile nanofibers as carriers, and electret nanoparticles and antibacterial nanoparticles are blended separately. The electret particles and antibacterial particles are evenly distributed without scattering or falling off, forming stable composite nanofibers.

[0038] Example 2 A method for preparing a nanofiber air filter material comprises the following steps: (1) Weigh 8.8 g of dimethylformamide solvent and place it in a 30 mL wide-mouth reagent bottle. Under magnetic stirring conditions, slowly add 0.15 g of the electret material BaTiO3 (average particle size of 50 nm) to 8.8 g of dimethylformamide solvent to obtain a dispersion. After ultrasonic treatment for 60 min using an ultrasonic cleaner, add 1.2 g of polyacrylonitrile powder, magnetically stir in a 45°C constant temperature water bath for 6 h, and then ultrasonically treat for 2 h to mix evenly until the first polymer is completely dissolved to obtain a PAN / BaTiO3 spinning solution; Weigh 8.8g of dimethylformamide solvent and place it in a 30mL wide-mouth reagent bottle. Under magnetic stirring conditions, slowly add 0.15g of antibacterial material ZnO (average particle size of 20nm) to 8.8g of dimethylformamide solvent to obtain a dispersion. After ultrasonic treatment for 60 minutes using an ultrasonic cleaner, add 1.2g of polyacrylonitrile powder, stir magnetically in a 45℃ constant temperature water bath for 6h, and then ultrasonically treat for 2h to mix evenly until the second polymer is completely dissolved to obtain a PAN / ZnO spinning solution.

[0039] (2) The obtained PAN / BaTiO3 spinning solution and PAN / ZnO spinning solution are respectively spun by independent injection pumps, and each of the injection pumps is connected to the syringe, catheter and needle in turn. The amount of PAN / ZnO spinning solution and PAN / BaTiO3 spinning solution is 5 mL. The devices and equipment used are the same as those in Example 1. Simultaneous electrospinning, the parameters are: spinning solution flow rate is 0.5 mL / h, spinning distance is 15 cm, spinning voltage is 20 kV, translation device moving speed is 200 cm / min, and receiving device speed is 80 rpm. Electrospinning is deposited on the receiving screen to obtain a nanofiber air filter material composite of PAN / ZnO and PAN / BaTiO3, with a thickness of 30 μm, a porosity of 86.7%, and an average fiber diameter of 595 nm.

[0040] Example 3 A method for preparing a nanofiber air filter material comprises the following steps: (1) Weigh 8.6 g of a mixed solvent of dimethylformamide and tetrahydrofuran (mass ratio of 1:1) and place it in a 30 mL wide-mouth reagent bottle. Under magnetic stirring conditions, slowly add 0.1 g of the electret material LiNbO3 (average particle size of 100 nm) to 8.6 g of a mixed solvent of dimethylformamide and tetrahydrofuran (mass ratio of 1:1) to obtain a dispersion. After using an ultrasonic cleaner to perform a circular ultrasonic treatment for 1 hour, add 1.4 g of polyvinylidene fluoride powder, stir magnetically in a constant temperature water bath at 50°C for 12 hours, and then perform ultrasonic treatment for 2 hours to mix evenly until the first polymer is completely dissolved to obtain a PVDF / LiNbO3 spinning solution; Weigh 8.6g of a mixed solvent of dimethylformamide and tetrahydrofuran (mass ratio of 1:1) and place it in a 30mL wide-mouth reagent bottle. Under magnetic stirring conditions, slowly add 0.2g of antibacterial material ZnO (average particle size of 20nm) to 8.6g of a mixed solvent of dimethylformamide and tetrahydrofuran (mass ratio of 1:1) to obtain a dispersion. After using an ultrasonic cleaner to perform a four-sided circular ultrasonic treatment for 1h, add 1.4g of polyacrylonitrile powder, stir magnetically in a constant temperature water bath at 50℃ for 12h, and then ultrasonically treat for 2h to mix evenly until the second polymer is completely dissolved to obtain a PVDF / ZnO spinning solution.

[0041] (2) The obtained PVDF / LiNbO3 spinning solution and PVDF / ZnO spinning solution are respectively spun by independent injection pumps, and each of the injection pumps is connected to the syringe, catheter and needle in turn. The amount of PVDF / ZnO spinning solution and PVDF / LiNbO3 spinning solution is 10mL. The devices and equipment used are the same as those in Example 1. Electrospinning is performed simultaneously, and the parameters are: spinning solution flow rate is 1 mL / h, spinning distance is 15cm, spinning voltage is 15 kV, translation device moving speed is 220 cm / min, and receiving device speed is 100 rpm. Electrospinning is deposited on the receiving screen to obtain a nanofiber air filter material composite of PVDF / ZnO and PVDF / LiNbO3, with a thickness of 20μm, a porosity of 85.3%, and a fiber average diameter of 465nm.

[0042] Example 4 A method for preparing a nanofiber air filter material comprises the following steps: (1) Weigh 8.6g of a mixed solvent of dimethylformamide and acetone (the mass ratio of dimethylformamide to acetone is 6:4) and place it in a wide-mouth reagent bottle. Under magnetic stirring conditions, slowly add 0.2g of the electret material LiNbO3 (average particle size is 80nm) to 8.6g of the mixed solvent of dimethylformamide and acetone (the mass ratio of dimethylformamide to acetone is 6:4) to obtain a dispersion. After using an ultrasonic cleaner to perform a circular ultrasonic treatment for 2h, add 1.4g of polyvinylidene fluoride powder, magnetically stir in a constant temperature water bath at 50℃ for 12h, and then ultrasonically treat for 2h to mix evenly until the polymer is completely dissolved to obtain a PVDF / LiNbO3 spinning solution; Weigh 8.6g of a mixed solvent of dimethylformamide and acetone (the mass ratio of dimethylformamide to acetone is 6:4) and place it in a wide-mouth reagent bottle. Under magnetic stirring conditions, slowly add 0.2g of the electret material BaTiO3 (average particle size of 50nm) to 8.6g of a mixed solvent of dimethylformamide and acetone (the mass ratio of dimethylformamide to acetone is 6:4) to obtain a dispersion. After using an ultrasonic cleaner to perform a circular ultrasonic treatment for 2h, add 1.4g of polyvinylidene fluoride powder, stir magnetically in a constant temperature water bath at 50℃ for 12h, and then ultrasonically treat for 2h to mix evenly until the polymer is completely dissolved to obtain a PVDF / BaTiO3 spinning solution; Weigh 8.8g of dimethylformamide solvent and place it in a wide-mouth reagent bottle. Under magnetic stirring conditions, slowly add 0.2g of antibacterial material TiO2 (average particle size of 20nm) to 8.8g of dimethylformamide solvent to obtain a dispersion. After using an ultrasonic cleaner to perform a four-sided circular ultrasonic treatment for 1h, add 1.2g of polyacrylonitrile powder, stir magnetically in a 50℃ constant temperature water bath for 12h, and then perform ultrasonic treatment for 2h to mix evenly until the second polymer is completely dissolved to obtain a PAN / TiO2 spinning solution.

[0043] (2) The obtained PVDF / LiNbO3 spinning solution, PVDF / BaTiO3 spinning solution and PAN / TiO2 spinning solution are respectively spun by independent injection pumps, and each of the injection pumps is connected to the syringe, the catheter and the needle in turn. The amount of PAN / TiO2 spinning solution, PVDF / BaTiO3 spinning solution and PVDF / LiNbO3 spinning solution is 5mL. The needles used are arranged in 3×3, and different spinning solutions in the same horizontal row are arranged in sequence, and the adjacent horizontal rows are arranged in a staggered manner, so that the electret particles and antibacterial particles are evenly distributed inside the membrane. The devices and equipment used are the same as those in Example 1. Simultaneous electrospinning, the parameters are: spinning solution flow rate is 1mL / h, spinning distance is 15cm, spinning voltage is 15 kV, translation device moving speed is 220 cm / min, and receiving device rotation speed is 100 rpm. Electrospinning was performed and deposited on a receiving screen to obtain PAN / TiO2, PVDF / BaTiO3 and PVDF / LiNbO3 composite nanofiber air filter materials with a thickness of 15 μm, a porosity of 83.4% and an average fiber diameter of 312 nm.

[0044] Comparative Example 1 (1) First, weigh 9 g of dimethylformamide solvent and place it in a 30 mL wide-mouth reagent bottle, then add 0.2 g of TiO2 (average particle size of 30 nm) and 0.2 g of BaTiO3 (average particle size of 50 nm), and stir magnetically to obtain a dispersion. After ultrasonic treatment for 60 min using an ultrasonic cleaner, add 1 g of polyacrylonitrile powder respectively, stir magnetically in a 45°C constant temperature water bath for 12 h, and then ultrasonically treat for 2 h to mix evenly until the polymer is completely dissolved to obtain a spinning solution.

[0045] (2) The electrospinning process, the device and the equipment used were the same as those in Example 1. The obtained nanofiber air filter material had a thickness of 25 μm, a porosity of 78.2% and an average fiber diameter of 692 nm.

[0046] Comparative Example 2 (1) Same as Example 1, except that the average particle size of BaTiO3 is 190 nm.

[0047] (2) The electrospinning process, the device and the equipment used were the same as those in Example 1. The obtained nanofiber air filter material had a thickness of 25 μm, a porosity of 76.9% and an average fiber diameter of 613 nm.

[0048] Comparative Example 3 PAN / BaTiO3 nanofiber air filter material was prepared with a thickness of 20 μm, an average fiber diameter of 192 nm, and a porosity of 78.6%.

[0049] Here are the steps: (1) First, weigh 9 g of dimethylformamide solvent and place it in a 30 mL wide-mouth reagent bottle, then weigh 0.75 g of BaTiO3 (average particle size of 30 nm), and slowly add BaTiO3 to the dimethylformamide solvent under magnetic stirring to obtain a dispersion. After ultrasonic treatment for 60 min using an ultrasonic cleaner, add 1 g of polyacrylonitrile powder, stir magnetically in a 45 ° C constant temperature water bath for 12 h, and then ultrasonically treat for 2 h to mix evenly until the polymer is completely dissolved to obtain a PAN / BaTiO3 spinning solution.

[0050] (2) The electrospinning process, the device and the equipment used are the same as those in Example 1.

[0051] Comparative Example 4 (1) Same as Example 3, except that the amount of ZnO added is 0.02 g.

[0052] (2) The electrospinning process, the device and the equipment used were the same as those in Example 3. A nanofiber air filter material was obtained with a thickness of 20 μm, a porosity of 82.7% and an average fiber diameter of 512 nm.

[0053] Electrical performance test: The contact separation piezoelectric performance test was performed on the filter materials obtained in Examples 1 to 4, Comparative Example 1 and Comparative Example 2, respectively. Figure 4 As shown, 13 is a linear motor, 14 is an electrometer, 15 is the negative electrode of the electrometer power supply, 16 is the positive electrode of the electrometer power supply, and 12 is a fiber membrane. Each fiber material sample and polypropylene spunbond nonwoven fabric 18 were cut into 5×5 cm 2 The squares were pasted onto two polytetrafluoroethylene plates 11, and the positive and negative electrodes of the electrometer 14 were connected from the positive and negative friction layer surfaces using copper foil strips 17. The contact frequency of the two polytetrafluoroethylene plates was set to 1 Hz, and the contact pressure was set to 30 N. The contact separation output voltage of each filter material was tested on the same day, the 7th day, and the 30th day, and the test results are shown in Table 1.

[0054] The output voltage of the composite material obtained in Example 1 was measured to be 9V (maximum output voltage) on the 7th day. Figure 5 shown.

[0055] Table 1

[0056] It can be concluded from Table 1 that the nanocomposite materials prepared in Examples 1 to 4 have good electret effect, and the output voltage does not drop significantly after 30 days, and has a long-term electret effect. This is mainly due to the addition of barium titanate and / or lithium niobate electret particles, and the preparation method of the present application improves the electrostatic adsorption performance of the fiber filter material.

[0057] Filtration performance test: According to the standard of GB / T 2626-2019 "Respiratory protection self-priming filter type anti-particulate respirator", the filtration performance of the filter materials obtained in Examples 1 to 4 and Comparative Examples 1 to 4 was tested respectively. Using TSI 8130A filter material tester, at 25±5°C and air flow rate (85±4) L / min, the filtration performance of each nanofiber material was tested for sodium chloride aerosol (count median particle size 0.075±0.02 μm, geometric standard deviation of particle size distribution ≤1.86, sodium chloride aerosol concentration 12~25 mg / m 3 ) filtration efficiency and filtration pressure drop. Each time, the composite nanofiber material was tapped for 1 minute with a hand wearing nitrile rubber gloves to activate its self-charging performance, and then the filtration performance test was performed. The filtration performance of each filter material was tested on the same day, 7th day and 30th day, and the test results are shown in Table 2.

[0058] Table 2

[0059] It can be concluded from Table 2 that the nanocomposites prepared in Examples 1 to 4 have both high filtration efficiency and low filtration pressure drop. The filtration efficiency on the day reached more than 95%, and the filtration pressure drop was 50 to 100 Pa, among which the filtration pressure drop of the nanocomposites prepared in Example 4 was smaller. Although the nanofiber materials prepared in Comparative Examples 3 to 4 have high filtration efficiency, the filtration pressure drop is large. This is because the nanofibers prepared in Comparative Example 3 have a smaller diameter, resulting in a denser fiber membrane, which increases the filtration pressure drop. The nanofibers prepared in Comparative Example 4 have a larger diameter, resulting in an increase in the inter-fiber gaps, which reduces the filtration pressure drop and reduces the filtration efficiency. The nanofiber materials prepared in Comparative Examples 3 and 4 are not suitable for actual production applications.

[0060] Antibacterial performance test: According to GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", the antibacterial properties of the filter materials obtained in Examples 1 to 4 and Comparative Examples 1 to 4 were tested against Escherichia coli and Staphylococcus aureus. The filter materials were irradiated with UVA light for 1 to 2 h in advance to activate the antibacterial particles to achieve a good antibacterial effect. The test results are shown in Table 3.

[0061] Table 3

[0062] It can be concluded from Table 3 that Examples 1 to 4 have good antibacterial effects, wherein the added titanium dioxide and / or zinc oxide have good antibacterial properties, and the ratio of each component is optimized according to the preparation method of the present application, and the nanofiber air filter material has both excellent electret effect and filtration effect, and stable properties. The antibacterial effect of the comparative example is poor and does not meet the antibacterial standard.

[0063] Although the present application has been described in detail above with general instructions and specific implementation schemes, it is obvious to those skilled in the art that some modifications or improvements can be made thereto based on the present application.

Claims

1. A method for preparing a nanofiber air filter material, characterized in that: The following steps are involved: Prepare an electret material spinning solution, disperse an electret material in a first solvent, then add a first polymer, and stir until the first polymer is completely dissolved to obtain a corresponding electret material spinning solution; wherein the electret material spinning solution includes one electret material spinning solution or several electret material spinning solutions, and the particle size of the electret material is 20nm~100nm; Prepare an antibacterial material spinning solution, disperse an antibacterial material in a second solvent, then add a second polymer, stir until the second polymer is completely dissolved, and obtain a corresponding antibacterial material spinning solution; wherein the antibacterial material spinning solution includes one antibacterial material spinning solution or several antibacterial material spinning solutions, and the particle size of the antibacterial material is 20nm~100nm; To prepare the nanofiber air filter material, the electret material spinning solution and the antibacterial material spinning solution are simultaneously electrospun to obtain the nanofiber air filter material; wherein the electret material spinning solution is supplied independently, and the antibacterial material spinning solution is supplied independently.

2. The method for preparing a nanofiber air filter material according to claim 1, characterized in that: The electret material is barium titanate and / or lithium niobate.

3. The method for preparing a nanofiber air filter material according to claim 1, characterized in that: The antibacterial material is titanium dioxide and / or zinc oxide.

4. The method for preparing a nanofiber air filter material according to claim 1, characterized in that: The first solvent is a dimethylformamide solution, a mixture of dimethylformamide and acetone, or a mixture of dimethylformamide and tetrahydrofuran; the second solvent is a dimethylformamide solution, a mixture of dimethylformamide and acetone, or a mixture of dimethylformamide and tetrahydrofuran.

5. The method for preparing a nanofiber air filter material according to claim 1, characterized in that: The amount of the electret material added is 0.5% to 2.5% of the mass of the electret material spinning solution, the amount of the antibacterial material added is 0.5% to 2.5% of the mass of the antibacterial material spinning solution, the mass concentration of the first polymer in the electret material spinning solution is 8% to 14%, and the mass concentration of the second polymer in the antibacterial material spinning solution is 8% to 14%.

6. The method for preparing a nanofiber air filter material according to claim 1, characterized in that: The first polymer is polyacrylonitrile and / or polyvinylidene fluoride, and the second polymer is polyacrylonitrile and / or polyvinylidene fluoride.

7. The method for preparing a nanofiber air filter material according to claim 1, characterized in that: The electret material spinning solution is independently supplied through a first injection pump, a first syringe, a first conduit and a first needle which are independently arranged in sequence; The antibacterial material spinning solution is independently supplied through a second injection pump, a second syringe, a second catheter and a second needle which are independently arranged in sequence.

8. The method for preparing a nanofiber air filter material according to claim 7, characterized in that: The direct current voltage of the electrospinning process is 10 kV~20 kV, the receiving distance is 7 cm~20 cm, the flow rate of the spinning solution is 0.5 mL / h~1 mL / h, and the moving speed of the moving device is 100 cm / min~400 cm / min.

9. A nanofiber air filter material, characterized in that: It is the nanofiber air filter material prepared according to the preparation method according to any one of claims 1 to 8.

10. The nanofiber air filter material according to claim 9, characterized in that: Its porosity is 80%~90%, thickness is 10μm~30μm, and average fiber diameter is 190nm~600nm.

Citation Information

Patent Citations

  • Composite anti-microbial air filtration material, preparation method and application

    CN104815483A

  • Multilayer electret nano-fiber filtering material and preparation method thereof

    CN107441827A

  • Micron fiber / nano fiber composited electret filter material and preparation method thereof

    CN107469466A

  • Deodorizing and antibacterial non-woven fabric for air purifier and preparation method of non-woven fabric

    CN116949682A